The role of social protection in preventing and managing food: Women’s and girls’ climate resilience - Hidrobo, Melissa; Roy, Shalini (socialprotection.org, 2025)
Social protection is increasingly recognised as a key policy tool to promote food security and resilience in crises, including those related to climate risk and conflict (Tenzing, 2020; Bruck et al., 2019). Awareness has also grown that gender must be considered to make agrifood systems more sustainable and resilient (Bryan et al., 2024). Yet, understanding remains limited on how to incorporate gender into the design of social protection to address food crises.